2021
DOI: 10.7150/thno.61711
|View full text |Cite
|
Sign up to set email alerts
|

The Polo-like kinase 1 inhibitor onvansertib represents a relevant treatment for head and neck squamous cell carcinoma resistant to cisplatin and radiotherapy

Abstract: Rationale: Head and neck squamous cell carcinoma (HNSCC) represent the 4 th most aggressive cancer. 50% of patients relapse to the current treatments combining surgery, radiotherapy and cisplatin and die two years after the diagnosis. Elevated expression of the polo-like kinase 1 (Plk1) correlated to a poor prognosis in epidermoid carcinomas. Methods: The molecular links between Plk1 and resistance to cisplatin/radiotherapy were investigated in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…PLK1 and AREG are highly expressed in HNSCC (Ling et al, 2021). Hagege et al reported that (Hagege et al, 2021) the expression of PLK1 was not determined by HPV status, which was consistent with our data. AREG , which is expressed when the DNA of stromal cells is damaged, induces programmed PD‐L1 expression in the receptor of carcinoma cells and produces immunologic suppression in the TME by activating the checkpoint to resist cytotoxic lymphocytes (Q. Xu, Long, et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…PLK1 and AREG are highly expressed in HNSCC (Ling et al, 2021). Hagege et al reported that (Hagege et al, 2021) the expression of PLK1 was not determined by HPV status, which was consistent with our data. AREG , which is expressed when the DNA of stromal cells is damaged, induces programmed PD‐L1 expression in the receptor of carcinoma cells and produces immunologic suppression in the TME by activating the checkpoint to resist cytotoxic lymphocytes (Q. Xu, Long, et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…PLK1 is reported to be overexpressed (at both mRNA and protein level) in many tumors compared to the normal tissue counterpart, and its overexpression has been associated with poor patient outcome ( 2 ). In addition, its overexpression has in some cases been associated with resistance to therapy and its inhibition to re-sensitization to chemo- and radio-therapy ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 dysregulation has been reported in different tumor types and its overexpression has been associated poor patients' outcome, resistance to chemotherapy and radiotherapy [11,[36][37][38]. However, the role of PLK1 in PTC pathogenesis is unclear.…”
Section: Discussionmentioning
confidence: 99%